(untitled) (Journal of Informatics Education and Research, 2025)
Financial technology (Fin Tech) has transformed the world financial system with incredible speed, introducing new age solutions in banking, lending, payments, and investment businesses. Fin Tech technologies driven by artificial intelligence, big data analytics, and block chain technology are making the financial system more efficient, transparent, and inclusive. This review article offers a comprehensive synthesis of twenty influential papers published between 2010 and 2024 that discuss the interface of Fin Tech, artificial intelligence, and financial inclusion. The review covers six broad thematic areas: Fin Tech business models, artificial intelligence and data analytics, crypto currency markets and peer-to-peer lending, small and medium-sized enterprises’ financial inclusion, governance and regulatory frameworks, and sustainability and ethics. Conceptual and theoretical contributions in Fin Tech stand firmly, but empirical evidence, cross-country analysis, and long-term assessment of social and economic effects of Fin Tech do not exist based on the research. To solve these deficiencies, a theoretical model is proposed to describe the interactions among technology drivers, Fin Tech mechanisms, and financial inclusion results, moderated by infrastructure, regulatory capacity, and customer confidence. The report concludes by presenting future research directions and policy recommendations focusing on responsible innovation, inclusive growth and sustainable financial systems.